THE APPLICATION OF JURISPRUDENTIAL LEARNING MODELS TO IMPROVE SOCIAL SKILLS AND STUDENTS LEARNING ACHIEVEMENT - Susi Andriani; Bambang Sahono; Turdjai Turdjai (DIADIK, 2018)
This research aims to (1) describe how to apply the jurisprudential learning models in improving students socialskill in social study lesson for 8 grade at SMPN 2 Tebing Tinggi, (2) to describe whether the application of the jurisprudential learning models could improve students learning achievement in social study lesson at SMPN 2 Tebing Tinggi, (3) to describe whether the effectiveness of Jurisprudential learning model application in improving students achievement in learning social study for the students at SMPN 2 Tebing Tinggi. This research conducted was classroom action research which combined with Quasi-experiment. The subject of this study were students of VIII SMPN 2 Tebing Tinggi. On this Research The data technique collection are use observation and Test. The technique of analysis data is  t- test. The condusion of outcome of The Research That Jurisprudential Model Learning effective for increase in social skill and student achievement.